70 Oesterreichische Kunstseelen Sprechen. (Wien : Das Offene Auge, 1986)
Damisch, Gunther ; Flois, Herbert ; Rainer, Helmut ; Reinhold, Thomas ; Scheibl, Hubert ; Strobl, Ingeborg ; Türtscher, Franz ; Vopava, Walter ; Danner, Gary ; Dunst, Heinrich ; Kopf, Willi ; Kowanz, Brigitte ; Mark, Helmut ; Rockenschaub, Gerwald ; Rose, Elisa ; Vana, Franz ; etc.
70 Oesterreichische Kunstseelen Sprechen, Das Offene Auge, Wien 20.04. - 07.06.1986
boek
Keywords: Oostenrijk